Novel azulene derivatives for the treatment of erectile dysfunction - Löber, Stefan; Hübner, Harald; Buschauer, Armin; Sanna, Fabrizio; Argiolas, Antonio; Melis, Maria Rosaria; Gmeiner, Peter (Bioorganic & Medicinal Chemistry Letters, 2012)
Based on the dopamine D receptor partial agonist FAUC 3019, a series of azulenylmethylpiperazines was synthesized and affinities for the monoaminergic GPCRs including dopamine, serotonin, histamine and α-adrenergic receptor subtypes were determined. Ligand efficacies of the most promising test compounds revealed the N,N-dimethylaminomethyl substituted azulene 11 to be the most potent D partial agonist (EC = 0.41 nM). This candidate was investigated for its ability to promote penile erection. Applying an in vivo animal model, test compound 11 turned out to stimulate penile erection in male rats with superior potency in low concentrations when compared to apomorphine. © 2012 Elsevier Ltd. All rights reserved.